Hydrogel-coated microneedle arrays for minimally invasive sampling and sensing of specific circulating nucleic acids from skin interstitial fluid - Al,Sulaiman D; Chang,JYH; Bennett,NR; Topouzi,H; Higgins,CA; Irvine,DJ; Ladame,S (ACS Nano, 2019)
Minimally invasive technologies that can sample and detect cell-free nucleic acid biomarkers from liquid biopsies have recently emerged as clinically useful for early diagnosis of a broad range of pathologies, including cancer. Although blood has so far been the most commonly interrogated bodily fluid, skin interstitial fluid has been mostly overlooked despite containing the same broad variety of molecular biomarkers originating from cells and surrounding blood capillaries. Emerging technologies to sample this fluid in a pain-free and minimally-invasive manner often take the form of microneedle patches. Herein, we developed microneedles that are coated with an alginate–peptide nucleic acid hybrid material for sequence-specific sampling, isolation, and detection of nucleic acid biomarkers from skin interstitial fluid. Characterized by fast sampling kinetics and large sampling capacity (∼6.5 μL in 2 min), this platform technology also enables the detection of specific nucleic acid biomarkers either on the patch itself or in solution after light-triggered release from the hydrogel. Considering the emergence of cell-free nucleic acids in bodily fluids as clinically informative biomarkers, platform technologies that can detect them in an automated and minimally invasive fashion have great potential for personalized diagnosis and longitudinal monitoring of patient-specific disease progression.